Interplay between polymerase II‐ and polymerase III‐assisted expression of overlapping genes. Issue 22 (7th October 2013) - Lukoszek, Radoslaw; Mueller-Roeber, Bernd; Ignatova, Zoya
Abstract : Up to 15% of the genes in different genomes overlap. This architecture, although beneficial for the genome size, represents an obstacle for simultaneous transcription of both genes. Here we analyze the interference between RNA‐polymerase II (Pol II) and RNA‐polymerase III (Pol III) when transcribing their target genes encoded on opposing strands within the same DNA fragment in Arabidopsis thaliana . The expression of a Pol II‐dependent protein‐coding gene negatively correlated with the transcription of a Pol III‐dependent, tRNA‐coding gene set. We suggest that the architecture of the overlapping genes introduces an additional layer of control of gene expression. Abstract : Overlapping genes from opposing strands are inversely transcribed. Polymerase II‐ and polymerase III‐assisted expressions negatively correlate. Overlapping genes introduce an additional layer to modulate gene expression.